Non-Performing Loan and How to Solve It - I Nyoman Alit Puspadma (Fakultas Hukum, Universitas Warmadewa, 2021)
Credit delivery by the bank requires the debtor to pay the obligations that have been scheduled in the credit agreement, but it will not always work well, sometimes because of something and other things there are also debtors who can not fulfill the obligations that have been promised so that credit problems occur. Non-performing loans also cause problems for banks, because they can make banks collapse. Thus the question arises, how to avoid the occurrence of problem loans and if it occurs, how is the solution?.